Coaching cues in amateur boxing: An analysis of ringside feedback provided between rounds of competition - Halperin, I.; Chapman, D. W.; Martin, D. T.; Abbiss, C.; Wulf, G. (Psychology of Sport and Exercise, 2016)
Feedback is commonly employed to enhance motor learning and performance. While numerous studies have investigated the causal effects of feedback on motor learning, an analysis of real-time feedback provided during training and competitive sporting environments is lacking. Therefore, the feedback provided by 12 boxing coaches to athletes between rounds of the 2015 Australian Boxing Championships was recorded and transcribed. The feedback statements were then analyzed according to three feedback variables that have been shown to be critical for optimizing performance: Attentional focus (external, internal, neutral), autonomy support (autonomy-supportive, controlling, neutral), and feedback valence (positive, negative, neutral). Collectively, 445 feedback statements provided during 25 bouts, of which 14 were won and 11 were lost, were analyzed for each of the three categories. Coaches provided on average 8 feedback statements per round. Excluding neutral statements, coaches delivered more internal (15%) compared with external focus feedback (6%), more controlling (53%) compared with autonomy-supportive feedback (6%), and more positive (29%) relative to negative feedback (12%). Furthermore, during winning bouts coaches delivered less internal (12% vs. 19%), less controlling (48% vs. 58%), and more positive (36% vs. 18%) feedback, when compared with losing bouts. These results demonstrate for the first time the type and frequency of feedback delivered during amateur boxing bouts. While these findings may or may not reflect causal relationships, it is interesting that feedback that has been found to enhance motor performance was more often used during winning rather than losing bouts.